Tetragenococcus halophilus, Staphylococcus xylosus and Staphylococcus saprophyticus for sardine fermentation - Zhijia Fang; Wenjuan Zhu; Ying Liu; Xinran Wang; Yaling Wang; Yanyan Wu (Czech Journal of Food Sciences, 2023)
To improve the quality and enrich the flavour of fermented sardine, Tetragenococcus halophilus, Staphylococcus xylosus, and Staphylococcus saprophyticus were used as a mixed starter for sardine fermentation. And their proportions were optimised using response surface methodology (RSM). The highest sensory score was obtained when the proportions of T. halophilus, S. xylosus, and S. saprophyticus were 1 : 1 : 1. The optimised fermented sardine had the lowest levels of histamine content (0.0190 μg.g-1), total volatile basic nitrogen (TVBN, 208 μg.g-1), and was richer in volatile compounds (308). The results may provide important evidence that T. halophilus, S. xylosus, and S. saprophyticus may be satisfactorily used as a mixed starter to improve the quality and flavour of fermented sardines.